PENGALIHAN ADMINISTRASI REKENING EFEK DALAM RANGKA PENGEMBALIAN IZIN USAHA ‘PERUSAHAAN EFEK’ - Budi Karisma (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to examine the legal protection provided to Securities Company customers, especially when transferring customer assets deposited by Securities Companies whose business licenses are revoked and to explain the process of claiming customer assets. This legal research is descriptive qualitative, using normative juridical research methods. Securities companies conducting their business activities based on a business license issued by the Financial Services Authority (OJK) may have their business license revoked by the OJK. The revocation of the business license will be accompanied by the closing of the Securities Account of the Securities Company. Securities Company customers who deposit their Securities with a Securities Company need to transfer their deposited Securities to another Securities Company. For customers who cannot be contacted, assets that have not been transferred by Securities Company customers will be transferred to the custodian of the Depository and Settlement Institution based on instructions from OJK. Until now, there is no regulation regarding the process of claiming customer assets whose Securities are deposited in the custodian of the Depository and Settlement Institution.